Glutathione S-transferase isoenzymes in human tumours and tumour derived cell lines. - Lewis, A. D. (Nature Publishing Group, 1989)
An increasing body of evidence indicates that glutathione S-transferases play a role in the intrinsic and acquired resistance of tumours to anticancer drugs. In view of the wide use of tumour cell lines to understand the factors which confer either sensitivity or resistance to chemotherapeutic agents we have determined glutathione S-transferase (GST) activity and isozyme composition in nine human cell lines. These data have been compared with the values obtained in solid tumours. In most cases overall GST activity was higher in the tumours than in the cell lines. This was most pronounced for the breast tumour samples relative to MCF7 cell line. The pi class GST subunit was present at similar concentration in the cell lines and the tumours, and in most cases was the most abundant subunit present. The alpha and mu class GST were expressed in most of the cell lines but at much lower concentration than the pi class subunit. Also considerable variability particularly in the expression of the mu subunits was observed. This was also the case for the expression of these subunits in the solid tumour samples. The levels of these GSTs (when expressed) in the solid tumours was invariably higher than that observed in the cell lines. There are therefore several similarities but also some significant differences in GST expression in solid tumours and cell lines. Whether the differences are because expression is lost during the generation of the cell lines or whether it reflects the individuality of human tumours remains to be clearly established. IMAGES: